Evaluating the protective effect of resveratrol, Q10, and alpha-lipoic acid on radiation-induced mice spermatogenesis injury: A histopathological study - Masoud Najafi; Mohsen Cheki; Peyman Amini; Abdolreza Javadi; Dheyauldeen Shabeeb; Ahmed Eleojo Musa (Shahid Sadoughi University of Medical Sciences, 2019)
Background Testis is one of the most sensitive organs against the toxic effect of ionizing radiation. Exposure to even a low dose of radiation during radiotherapy, diagnostic radiology, or a radiological event could pose a threat to spermatogenesis. This may lead to temporary or permanent infertility or even transfer of genomic instability to the next generations. Objective In this study, we evaluated the protective effect of treatment with three natural antioxidants; resveratrol, alpha lipoic acid, and coenzyme Q10 on radiation-induced spermatogenesis injury. Materials and Methods 30 NMRI mice (6-8 wk, 30 ± 5 gr) were randomly divided into six groups (n = 5/each) as 1) control; 2) radiation; 3) radiation + resveratrol; 4) radiation + alpha lipoic acid; 5) radiation + resveratrol + alpha lipoic acid; and 6) radiation+ Q10. Mice were treated with 100 mg/kg resveratrol or 200 mg/kg alpha lipoic acid or a combination of these drugs. Also, Q10 was administered at 200 mg/kg. All treatments were performed daily from two days before to 30 min before irradiation. Afterward, mice were exposed to 2 Gy 60 Co gamma rays; 37 days after irradiation, the testicular samples were collected and evaluated for histopathological parameters. Results Results showed that these agents are able to alleviate some toxicological parameters such as basal lamina and epididymis decreased sperm density. Also, all agents were able to increase Johnsen score. However, they could not protect against radiation-induced edema, atrophy of seminiferous tubules, and hyperplasia in Leydig cells. Conclusion This study indicates that resveratrol, alpha-lipoic acid, and Q10 have the potential to reduce some of the side effects of radiation on mice spermatogenesis. However, they cannot protect Leydig cells as a source of testosterone and seminiferous tubules as the location of sperm maturation.